Can physical activity interventions for adults with type 2 diabetes be translated into practice settings? A systematic review using the RE-AIM framework. Issue 1 (26th September 2013) - Matthews, Lynsay; Kirk, Alison; MacMillan, Freya; Mutrie, Nanette
ABSTRACT: Despite the strong evidence base for the efficacy of physical activity in the management of type 2 diabetes, a limited number of physical activity interventions have been translated and evaluated in everyday practice. This systematic review aimed to report the findings of studies in which an intervention, containing physical activity promotion as a component, has been delivered within routine diabetes care. A comprehensive search was conducted for articles reporting process data relating to components of the RE-AIM (Reach, Effectiveness, Adoption, Implementation and/or Maintenance) framework. Twelve studies met the selection criteria. Of the nine studies which measured physical activity as an outcome, eight reported an increase in physical activity levels, five of which were significant. Tailoring recruitment, resources and intervention delivery to the target population played a positive role, in addition to the use of external organisations and staff training. Many interventions were of short duration and lacked long-term follow-up data. Findings revealed limited and inconsistent reporting of useful process data.